Carbohydrate-Based Organocatalysts: Recent Developments and Future Perspectives - Mishra, Amrita; Mishra, Nidhi; K. Tiwari, Vinod (Current Organic Synthesis, 2016)
Organocatalysts are small organic molecules that accelerate a reaction when used in sub-stoichiometric amounts. Their utility in various synthetically useful transformations have increased enormously in the past decade. Representing a link between two major forms of catalysis: metal complex mediated catalysis and enzymatic catalysis, the term ‘organocatalysis’ establishes connectivity between synthetic and bioorganic chemistry. Despite the enormous utility and selectivity of organocatalysts, there are very few selected basic substrates which have proven to be potent scaffolds for organocatalyts. Carbohydrate moiety due to its ready availability, high functionality, several stereogenic centers and other fascinating structural aspects, provides accessibility for the synthesis of series of chiral ligands that are highly selective for particular reactions. Hence, chirality and functional diversity are the key features due to which sugar moiety might prove to be a potent scaffold for metal free catalysis. A number of stereospecific reactions can be accelerated by carbohydrate based chiral molecules. Due to these reasons carbohydrate moiety has recently emerged from relative obscurity to prominence as highly efficient substrates for the synthesis of organocatalysts which furnishes products with high enantioselectivity. This review highlights the basic aspects and recent impressive progress in the area of carbohydrate based organocatalysts as well as organo-catalytic reactions. The different carbohydrate based organocatalysts have been classified on the basis of their chemical structures and functionalities.
Keywords: Carbohydrate